Upaya Peningkatan Status Gizi Balita Melalui Edukasi Menu MPASI Sesuai Tahapan Usia - Sitti Aras Diana; Nur Anita (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Nutritional problems among children under five (toddlers) remain one of the major public health challenges that require special attention, particularly regarding the provision of complementary feeding (Makanan Pendamping ASI/MP-ASI) that is appropriate to the child’s age stage. A lack of maternal knowledge regarding the types, texture, frequency, and nutritional content of MP-ASI can affect a child’s nutritional status as well as their growth and development process. This condition was also identified in the community of Daala Timur Village, Bulo Subdistrict, Polewali Mandar Regency. Therefore, this community service activity was conducted as an effort to improve the nutritional status of toddlers through education on MP-ASI menus according to age stages.The implementation method of this activity was carried out in the form of health education for mothers of toddlers using educational media in the form of presentation materials covering the definition of MP-ASI, the appropriate age to introduce MP-ASI, risks of introducing MP-ASI too early, and appropriate texture stages of MP-ASI based on age groups. The material delivered included the concept of MP-ASI, stages of complementary feeding according to age, principles of balanced nutrition menus, and simple menu examples that can be applied at home. The activity also included discussion and question-and-answer sessions between the presenter and participants to improve participants’ understanding of the delivered material.The community service activity was conducted smoothly and received high enthusiasm from the participants. The mothers of toddlers showed active attention and engagement throughout the counseling session. Through this activity, it is expected that mothers will better understand the importance of providing MP-ASI according to age stages as one of the efforts to support the growth, development, and improvement of toddlers’ nutritional status.